2008
DOI: 10.1007/bf03161209
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative and sympathomimetic toxicity associated with recreational use of 1-(3-trifluoromethylphenyl) piperazine (TFMPP) and 1-benzylpiperzine (BZP)

Abstract: Introduction: There is emerging evidence of increasing use of legally available synthetic compounds as recreational drugs. While there are some changes to legislation relating to these synthetic compounds, often the emergence of the agents outpaces the effect of the legislation to curb their use, and the legal status of these agents may change as more information on their toxicity becomes known. TFMPP [1-(3-trifluoromethylphenyl) piperazine] was initially temporarily controlled under Schedule I of the Controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 11 publications
1
62
0
1
Order By: Relevance
“…We have previously reported the benefits of proactive ad hoc toxicological screening in individuals who self-report the use of "novel" drugs [23][24][25][26]. Detailed toxicological screening in these cases has established that the presentations were related to the use of a novel drug and contribute to the understanding of the potential toxicity of novel drugs as they enter the recreational drug scene.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the benefits of proactive ad hoc toxicological screening in individuals who self-report the use of "novel" drugs [23][24][25][26]. Detailed toxicological screening in these cases has established that the presentations were related to the use of a novel drug and contribute to the understanding of the potential toxicity of novel drugs as they enter the recreational drug scene.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have similar pharmacological properties to the popular stimulants such as cocaine, amphetamines and 3,4-methylenedioxy-N-methylamphetamine (MDMA) [4][5][6][7][8][9]. Toxicity [10][11][12][13][14] and some deaths [15][16][17] have been associated with the recreational use of these drugs. These drugs are sometimes sold online under a variety of names, such as "bath salts" and "plant food" [18], and users often do not know the actual active ingredients when using these drugs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity [10][11][12][13][14] and some deaths [15][16][17] have been associated with the recreational use of these drugs. These drugs are sometimes sold online under a variety of names, such as "bath salts" and "plant food" [18], and users often do not know the actual active ingredients when using these drugs [12].…”
Section: Introductionmentioning
confidence: 99%
“…We have already reported that proactive ad hoc toxicological screening undertaken in recreational drug presentations, in which individuals self-report ingestion of novel drugs or have atypical presentations following ingestion of classical recreational drugs, can detect a range of novel or emerging recreational drugs [1][2][3][4][5]. This case also highlights that research chemical compounds, such as Bromo-dragonFLY, may also enter the recreational drug market.…”
Section: Discussionmentioning
confidence: 82%
“…In spite of this legislation, there have been many recent reports of toxicity associated with emerging "novel" recreational drugs or pharmaceutical agents misused as recreational drugs [1][2][3][4][5][6]. Often the legislation concerning these novel recreational drugs is inconsistent, with control only occurring in a limited number of countries [4].…”
Section: Introductionmentioning
confidence: 99%